Factors associated with the continuity of prenatal care among pregnant women in the health zone of Kingasani, Kinshasa, Democratic Republic of the Congo - Badibake, Agnes Tudinange; Bukasa, Augustin Kadiata; Leyka, Mukandu Basua Babintu; Omanyondo, Ohambe Marie-Claire (Orapuh Journal, 2024)
Introduction Antenatal care provides a platform for important health benefits, including health promotion, screening, diagnosis, and disease prevention. It is established that timely implementation of appropriate evidence-based practices in antenatal care can save lives. PurposeThis study aimed to identify factors associated with the continuity of prenatal care among pregnant women in the Kingasani Health Zone. Methods This descriptive correlational study used proportional stratified sampling to select participants and collect data from February 20, 2021, to April 5, 2021. A total of 165 subjects were included in the study. Results The analysis revealed that the continuity of prenatal care is statistically linked to the delay in initiation of ANC (RR: 2.108, 95% CI [1.334-3.332], χ2: 13.780, p < 0.0001), encouragement of women to follow ANC (χ2: 5.643, p = 0.007), and compliance with appointments by pregnant women (RR: 3.143, 95% CI [1.106-8.901], χ2: 8.189, p = 0.004). However, continuity of antenatal care is not linked to the distance between home and the antenatal care service (RR: 2.188, 95% CI [1.002-5.377], χ2: 5.866, p = 0.015). These findings partially confirm that the use of prenatal services in the Kingasani Health Zone is positively influenced by the personal characteristics of the subjects. Conclusion Prenatal care providers have a major task in explaining to pregnant women the number of ANC visits scheduled for a pregnancy, their frequency, the importance, and the principles of each ANC activity. Evaluating the quality of ANC and the frequency of ANC clients at referral health centers is crucial.